Pengaruh Budaya Kaizen Dan Disiplin Kerja Terhadap Kinerja Karyawan Di BCA KFKK Malang - Permana, Cahya Dwi Hendra; Rachma, N.; Mustapita, Arini Fitria (UNIVERSITAS ISLAM MALANG, 2024)
AbstractÂ This study aims to examine the Influence of Kaizen Culture and Work Discipline on Employee Performance at BCA KFKK Malang. The population and sample in this study were 60 respondents, with a saturated sample method. Data were collected through questionnaires distributed online. The data analysis method used in this study is quantitative data analysis using multiple linear regression analysis, determination analysis, simultaneous test (F) and partial test (t). The results of simultaneous testing indicate that kaizen culture and work discipline have a significant effect on employee performance. Based on the partial test, kaizen culture has a significant effect on employee performance, and partially work discipline has a significant effect on employee performance.Â Keywords: Kaizen Culture, Work Discipline, and Employee Performance